Co-delivery of Doxorubicin and PSC 833 (Valspodar) by Stealth Nanoliposomes for Efficient Overcoming of Multidrug Resistance - Elmira Bajelan; Azadeh Haeri; Amir Masoud Vali; Seyed Nasser Ostad; Simin Dadashzadeh (Frontiers Media S.A., 2012)
Purpose. This study was aimed at developing co-encapsulated stealth nanoliposomes containing PSC 833, an efficient MDR modulator, and doxorubicin (DOX) in order to increase the effectiveness and decrease adverse effects of the anticancer drug. Methods. In attempt to increase the encapsulation efficiency of drugs, different methods for liposome preparation were tested and the effect of different parameters such as drug to lipid molar ratio, cholesterol mole percent and lipid compositions, were investigated. The final product with a lipid composition of EPC:DSPE-PEG2000:Chol (60:5:30 %mol) was prepared by thin layer film hydration method. After preparation of empty liposomes, DOX and PSC 833 were loaded using ammonium sulfate gradient and remote film loading methods, respectively. Physical characteristics of optimized liposomes (DOX/PSC-L) such as particle size, zeta potential, encapsulation efficiency, in-vitro drugs release and stability were evaluated. Furthermore, in vitro cytotoxicity study of various liposomal formulations as well as drugs, solutions against resistant human breast cancer cell line, T47D/TAMR-6, was evaluated using MTT assay. Results. The best formulation showed a narrow size distribution with average diameter of 91.3 ± 0.2 nm with zeta potential of -6 ± 1.2, the encapsulation efficiency for DOX and PSC 833 were more than 95% and 65.5%, respectively. In DOX-resistant T47D/TAMR-6 cells, dual-agent stealth liposomes showed significantly greater cytotoxicity (P < 0.05) than free DOX and liposomal DOX plus free PSC 833 treatments. Conclusions. Co-encapsulation of DOX and PSC 833 presents a promising anticancer formulation, capable of effective reversal of drug resistance, and should be explored further in therapeutic studies with animal tumor xenograft models. This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.